The Effect of Welfare, Work Motivation and Education Level on Personnel Performance in the Cimahi Resort Police Security Intelligence Unit - Dimas Pambudi; Yuni Pratikno; Sitta Kusuma (Dinasti Publisher, 2026)
Personnel performance is an important factor in supporting the effectiveness of intelligence and security tasks, especially in the Security Intelligence Unit of the Cimahi Police Resort which has a strategic role in maintaining regional stability and security. Optimal personnel performance is influenced by various internal organizational factors, including welfare, work motivation, and education level. This study aims to analyze the influence of welfare on personnel performance, the influence of motivation on personnel performance, the influence of education level on personnel performance, and the influence of welfare, motivation, and education level simultaneously on personnel performance in the Security Intelligence Unit of the Cimahi Police Resort. This study uses a quantitative approach with a survey method, which emphasizes the collection and processing of data in the form of numbers so that the results of the analysis can be interpreted objectively and measurably. In addition, this study is supplemented with qualitative data as supporting data, in the form of open-ended statements in questionnaires and the results of consultations and short interviews to enrich understanding of the variables studied. The study population was 53 personnel, with the sampling technique using total sampling. Data analysis was conducted using multiple linear regression with the help of the SPSS Version 26 program. The results showed that partially welfare and education level had a positive and significant effect on personnel performance, while motivation did not have a significant effect on personnel performance. Simultaneously, welfare, motivation, and education level influence personnel performance. The coefficient of determination (R Square) value of 0.508 indicates that 50.8% of the variation in personnel performance can be explained by these three variables, while the remainder is influenced by other factors outside the research model. This finding confirms that improving welfare and education level are strategic factors in improving the performance of personnel of the Cimahi Police Security Intelligence Unit